NILAI BERITA PADA PEMBERITAAN BISNIS PORTAL BERTUAHPOS.COM - ismandianto, ismandianto; Wahidar, Tutut Ismi; Devitriana , Nur (Medium: Jurnal Ilmiah Fakultas Ilmu Komunikasi, 2021)
News value is one of the compulsory components in news, be it print media (newspapers, tabloids), electronic media (television, radio) or online media. PT. Citra Media Bertuah or Bertuahpos.com is one of the online media in Pekanbaru that focuses on business news as much as 75%. Bertuahpos.com is also one of 300 online media in Riau which has been verified as actual and factual by the Press Council. In its implementation there are still some news which according to the author is not comprehensive because it does not contain news value properly. This research method is a qualitative descriptive analysis. In this study the authors searched through documentation in the form of theoretical data from books, document data in the form of formal notes, news portal bertuahpos.com related to the discussion of this thesis, internet and so on with regard to the title. Observations were also made to the Bertuahpos office to meet references regarding supporting data in completing this thesis. The results of this study indicate that Bertuahpos has applied news values ​​greatly. Of the 23 news stories that the author studied, there are at least 7 news values ​​that have been applied by Bertuahpos from 8 news values ​​from Hariris, Leiter and Johnson which are indicators of the author's research. The 7 news values ​​are actual, important, progress, closeness, impact, conflict, and humane.